2021
DOI: 10.1016/j.heliyon.2021.e08510
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the adversity quotient on student performance, student learning autonomy and student achievement in the COVID-19 pandemic era: evidence from Indonesia

Abstract: This research investigates the effects of the adversity quotient introduced by Paul G. Stoltz on students achievement motivation, student learning autonomy and student performance. The study was conducted through an online survey with 218 participants from selected students of two Islamic senior high school in Indonesia. Data and information gathering from respondent analyzed by partial least square structural modelling using SmartPLS. This research revealed that adversity quotient were significant constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
16

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 21 publications
4
24
0
16
Order By: Relevance
“…In other words, the adversity quotient helped students respond to difficulties in online learning positively, hence minimizing academic procrastination behavior. This finding supported earlier research on 218 state Madrasah Aliyah students in Pontianak, Indonesia, according to which adversity quotient influenced students' adaptability from offline to online learning, including in terms of the ability to access and use online learning to establish a learning standard (Safi'i et al, 2021). Students with a higher adversity quotient found it easier to deal with any problems (Parvathy and Praseeda, 2014).…”
Section: Coefficient (β ) P-valuesupporting
confidence: 88%
See 2 more Smart Citations
“…In other words, the adversity quotient helped students respond to difficulties in online learning positively, hence minimizing academic procrastination behavior. This finding supported earlier research on 218 state Madrasah Aliyah students in Pontianak, Indonesia, according to which adversity quotient influenced students' adaptability from offline to online learning, including in terms of the ability to access and use online learning to establish a learning standard (Safi'i et al, 2021). Students with a higher adversity quotient found it easier to deal with any problems (Parvathy and Praseeda, 2014).…”
Section: Coefficient (β ) P-valuesupporting
confidence: 88%
“…In contrast, those with low adversity quotients will tend to give up and yield easily display pessimism, and exhibit a negative attitude (Stoltz, 2006). Earlier research findings showed that the adversity quotient affected students' ability to adapt to online learning from offline learning, not excluding the ability to access and use online learning to establish a learning standard (Safi'i et al, 2021).…”
Section: The Effects Of Parental Social Support and Adversity Quotien...mentioning
confidence: 99%
See 1 more Smart Citation
“…AQ juga berpengaruh pada kemampuan siswa dalam pemahaman konsep matematis, pemecahan masalah, berpikir kritis, berpikir kreatif, penalaran kreatif, prestasi belajar, kepercayaan diri, kemandirian belajar, dan motivasi berprestasi (Annikmah et al, 2020;Ardyanti & Harini, 2015;Darmawan et al, 2019;Dewanto et al, 2019;Handayani & Ramadhani, 2020;Lusiana et al, 2021;Nahrowi et al, 2020;Rahayu & Alyani, 2020;Safi'i et al, 2021;Suhandoyo, 2016).…”
Section: Synthesis Resultsunclassified
“…Selain itu, AQ dan kreativitas dapat mempengaruhi pemecahan masalah (Suhendri & Ningsih, 2018). Penelitian lainnya menunjukkan bahwa AQ merupakan konstruk yang berpengaruh terhadap prestasi, kemandirian, serta motivasi berprestasi belajar (Safi'i et al, 2021). Dengan demikian, kesuksesan siswa mempelajari matematika dipengaruhi oleh AQ.…”
Section: Pendahuluanunclassified